Comprehensive analysis of gene expression in human retina and supporting tissues - Li, Mingyao (Hum Mol Genet, 2014)
Understanding the influence of gene expression on the molecular mechanisms underpinning human phenotypic diversity is fundamental to being able to predict health outcomes and treat disease. We have carried out whole transcriptome expression analysis on a series of eight normal human postmortem eyes by RNA sequencing. Here we present data showing that ∼80% of the transcriptome is expressed in the posterior layers of the eye and that there is significant differential expression not only between the layers of the posterior part of the eye but also between locations of a tissue layer. These differences in expression also extend to alternative splicing and splicing factors. Differentially expressed genes are enriched for genes associated with psychiatric, immune and cardiovascular disorders. Enrichment categories for gene ontology included ion transport, synaptic transmission and visual and sensory perception. Lastly, allele-specific expression was found to be significant forCFH,C3 andCFB, which are known risk genes for age-related macular degeneration. These expression differences should be useful in determining the underlying biology of associations with common diseases of the human retina, retinal pigment epithelium and choroid and in guiding the analysis of the genomic regions involved in the control of normal gene expression.